Effect of Different Types of Biochar Applications and Phosphate Fertilizer on the Quality and Yield of Edamame Soybeans on Andisols - Ramdhana Karimah; Benito Heru Purwanto; Eko Hanudin; Sri Nuryani Hidayah Utami; Margi Asih Maimunah (Universitas Sebelas Maret, 2024)
Edamame soybean (Glycine max (L.) Merr.) cultivation in phosphorus-limited Andisols presents a formidable challenge due to restricted phosphorus availability despite high phosphorus retention. Unlocking the full potential of this crop demands innovative solutions. This study delves into the transformative effects of biochar and phosphorus fertilizer, individually and synergistically, on edamame soybean growth in Andisols. Employing a randomized complete block design, researchers investigate three types of biochar (B0: control, B1: biochar pellets, B2: biochar powder) and four phosphorus fertilizer rates (P0: control, P1: 27 kg ha-1 P2O5, P2: 54 kg ha-1 P2O5, P3: 81 kg ha-1 P2O5). The bamboo-derived biochar was produced using the Kon-tiki method at ±500 °C. The study reveals no significant interaction between biochar and phosphorus fertilizer. Individually, treatments with B1, B2, and phosphorus fertilizers significantly enhance ammonium, nitrate, and phosphorus availability compared to B0 and P0. Biochar-induced modifications improve phosphorus and nitrogen absorption by roots, resulting in increased shoot dry weight and the root/shoot ratio. However, the number of leaves is solely influenced by phosphorus fertilizer treatment. Additionally, both biochar and phosphorus fertilizers contribute to nitrate reductase activity, root volume, an increased number of pods per plant and higher protein content in edamame soybeans. B2 outperforms B1 and high P3 intensifies this effect, improving nutrient uptake and yield. In summary, biochar and phosphorus fertilizers demonstrate significant potential to revolutionize edamame soybean cultivation in phosphorus-limited Andisols, optimizing pod number per plant and enhancing quality with elevated protein content.